A chronic case of Madurella mycetoma involving left foot - Alim, Alfia; Pati, Binod K.; Sarfraz, Asim; Das, Sushmita (International Journal of Research in Medical Sciences, 2019)
Mycetoma is a localized chronic, suppurative, and deforming granulomatous disorder of subcutaneous tissue, skin and bones. Mycetoma is endemic in tropical and subtropical areas, where it is a real public health issue. It is a rare and neglected disease in our country. Etiological classification divides it into eumycetoma caused by fungus, and actinomycetoma caused by bacteria. Since the treatment of these two etiologies is completely different, a definite diagnosis after microbiological and histopathological examination, though difficult, is important. The disease is notoriously difficult to treat. Eumycetoma may be unresponsive to standard antifungal therapy. Authors report a case of eumycetoma in a 38 year-old male from Bihar, with history of thorn prick 30 yrs back. Madurella mycetomatis was isolated from the granular discharge from sinuses and itraconazole was given followed by surgical debridement of the lesion. The patient recovered well and is still on follow up.